Peculiarities of Aerobic Capacity of Military Academy Students (Baltic Journal of Sport and Health Sciences, 2018)
The aim of the study was to evaluate the aerobic capacity of the first year students in the Lithuanian Military Academy.63 first year students (57 men and 6 women) agreed to participate in the study. They performed graded cycling exercisetest until voluntary exhaustion. The starting work load was set at 70 W and was increased every minute by 21 W.Pulmonary gas exchange was measured breath-by-breath using the portable telemetric system (Oxycon Mobile,Jaeger). The maximal oxygen uptake (VO 2  max) was determined as the highest VO 2  within 20 s period obtained duringincreasing cycling test. Maximal cardiorespiratory values at this point were calculated as well. The VO 2  max in militaryacademy cadets was 52.9 (4.6) ml / kg -1  / min -1  (from 42.7 to 63.4). The aerobic capacity in most cadets may beconsidered as high and very high (80%), and only in one fifth of the subjects — as moderate, applying the normativescale for untrained persons.Keywords: maximal oxygen uptake, aerobic capacity, cycling ergometry.